Connotative meaning and translation issues - Kamalyan, Arevik (Bulletin of Yerevan University B: Philology, 2021)
Connotation is one of the most challenging aspects in translation. This paper highlights the importance of connotative meaning in literary translation. In this paper we examine difference between connotative meanings in Armenian and Russian languages and present a number of translated examples from Armenian into Russian and vice versa.
Keywords: connotation; connotative meaning translation; political correctness; euphemism; background knowledge; associations; symbolism; cross-cultural communication